2018
DOI: 10.1007/s40415-018-0492-6
|View full text |Cite
|
Sign up to set email alerts
|

Plant species richness record in Brazilian Pampa grasslands and implications

Abstract: Species richness remains one of the most valuable type of information for biodiversity conservation. Here, we report a plant richness record in the Brazilian Pampa. We found 56 vascular plant species in a single plot of 1 9 1 m in a privately owned grazed grassland in a region with shallow soils. This number is considerably higher than common species numbers in similar surveys and highlights the high plant diversity in South Brazilian grasslands. We take our record as an opportunity to reflect on some issues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
0
6
0
2
Order By: Relevance
“…Unfortunately, the lack of funding and incentives for this kind of study is a known problem (VOGEL ELY et al, 2017;MENEZES et al, 2018, SALDAÑA et al, 2018. Even so, we emphasize that an investment in sampling efforts, especially in Araucaria Forest, is necessary to ensure effective conservation actions for endangered species such as V. linostigma.…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, the lack of funding and incentives for this kind of study is a known problem (VOGEL ELY et al, 2017;MENEZES et al, 2018, SALDAÑA et al, 2018. Even so, we emphasize that an investment in sampling efforts, especially in Araucaria Forest, is necessary to ensure effective conservation actions for endangered species such as V. linostigma.…”
Section: Discussionmentioning
confidence: 97%
“…This Brazilian state is remarkable because it holds two contrasting biomes: the Atlantic Rain Forest and the Pampas. The Pampas Biome, in Brazil, is restricted to Rio Grande do Sul State but is also shared with neighboring countries such as Argentina and Uruguay [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Pampa vegetation has always been neglected until recent research revealed remarkable records of plant diversity [ 5 ]. Of 65 cacti species native to Rio Grande do Sul, 53 (81.53%) are threatened with extinction according to IUCN criteria and most of them occur in rocky outcrops of the Pampa [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Behind the apparently uniformity of the Pampa, studies found that this domain is highly diverse. For instance, Menezes et al [6] recorded 56 plant species per square meter within their native vegetation. Likewise, the soil organism richness is quite high in native grasslands, such as for springtails, beetles and spiders [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%